Actors and social relationships in the social construction of markets in the Alto Uruguai Nucleus of the Ecovida Agroecolgy Network (Rede Ecovida) (Desenvolvimento em Questão, 2024)
The markets are increasingly becoming part of the daily lives of family farmers, but there are still obstacles to their participation in these spaces. Organizations like the Ecovida Agroecology Network (REDE ECOVIDA) are trying to create conditions to address these challenges and promote rural development, making it an important field of study, especially for understanding its dynamics. Thus, this work aims to characterize the social and institutional network of relationships that influence the markets of family farmers in the Alto Uruguai Nucleus of the Ecovida Network. In order to meet the research objective, Mark Granovetter’s social network theory was applied, which helps to identify and elucidate actors and social networks. The research is characterized as descriptive, and primary data Generation was based on semi-structured interviews with the entities that make up the Nucleus and on systematic non-participant observation of the meetings of five farmers groups within the Core. Secondary data were collected through documentary research. The main findings reveal that farmers in the Alto Uruguai Nucleus constitute an extensive social network, involving social and institutional, individual and collective actors, as well as those external and internal to the Nucleus - which influence the farmers markets in different ways. Based on these results, it can be inferred that the development of alternative markets has been an importante strategy used by family farmers and organizations, and that social network analysis is a valuable tool for interpreting family farming markets.
Keywords: Markets; Social relationships; Social actors